Prospective assessment of a gene signature potentially predictive of clinical benefit in metastatic melanoma patients following MAGE-A3 immunotherapeutic (PREDICT) - Saiag, Philippe; Gutzmer, R.; Ascierto, P. A.; Maio, M.; Grob, J. -J.; Murawa, P.; Dreno, B.; Ross, M.; Weber, J.; Hauschild, A.; Rutkowski, P.; Testori, A.; et al. (Annals of oncology, 2016)
Genomic profiling of tumor tissue may identify gene signatures (GS) predictive of tumor response to treatment. We prospectively evaluated a GS linked to clinical benefit following MAGE-A3 immunotherapeutic in patients with advanced melanoma. One-year overall survival was similar in patients with and without the GS: the GS was not predictive of outcome after MAGE-A3 immunotherapeutic treatment.
Das PDF enthält nur die 1. Seite des Artikels
Gesehen am 07.05.2020